STRESSED OUT IN WHITE COATS: A STUDY ON PERCEIVED STRESS AND STRESSORS IN UNDERGRADUATE MEDICAL STUDENTS (Journal of Forensic Medicine & Toxicology, 2025)
Stress among medical students across the world has emerged as a major cause of concern over last few years. Multiple studies across the globe have shown a significant high stress level among medical students. This cross-sectional study was conducted in a medical college in eastern India among one hundred and twenty eight medical undergraduate students in their seventh semester. Data was collected using self-administered questionnaire for demographic details, academic, psychosocial and environmental stressors and perceived stress scale (PSS). Out of the 128 students who participated, 72 (56.25% ) were female and 56 (43.75%) were male. The mean perceived stress score was 27.18 +/- 5.68. The median perceived stress score of the observations was 28. Mean perceived stress scores among female and male medical students were 28.52+/- 5.42 and 25.82+/- 5.15 respectively. Majority of both male and female students
Keywords: Perceived stress; Medical college; Undergraduate students